A comparison of the behind armour blunt trauma effects between ceramic faced and soft body armours caused by ballistic impact - Lewis, E. A.; Horsfall, Ian; Watson, Celia H. (Cranfield University, 2002)
Recently published research has characterised the behind armour blunt trauma (BABT) effects associated with high velocity ballistic impact on textile-based armour faced with a ceramic plate. Subsequently dynamic displacements, accelerations and pressures have been characterised both in Gelatine experiments and animal experiments and used to provide test methodologies. High velocity armour consists of a ceramic plate usually backed with a composite panel, which is worn over the conventional textile body armour. The purpose of the plate is to disrupt and spread the energy of the high velocity projectile such that the resulting displacement can beaccommodated and partially absorbed by the textile armour. On its own, the textile armour isonly capable of preventing penetration by low kinetic energy density projectiles such as fragments, which are of a similar magnitude to hand gun bullets. For police officers, civilian security personnel and for the military, in operations other than war, there is a need to protect against low-velocity handgun bullets such as 9mm and 0.375 Magnum; these being the rounds typically used in ballistic test standards. As the purpose of the ceramic plate is to reduce the energy density of a high-velocity projectile to that which can be arrested bya soft armour; it follows that there may be a relationship between the impact of a low-velocity projectile on soft armour and a high velocity projectile on a ceramic faced soft armour .The purpose of this work was to gather data on the back-face deformation behaviour of soft body armour and compare it to that of hard armour by determining whether there was a correlation between previous ceramic plate data and soft armour tests, and also to determine whether backface pressure data could be used to rank other simulant materials.